Penggunakan Metode Kooperatif Learning pada Materi ASEAN IPS Sekolah Dasar untuk Meningkatkan Hasil Belajar - Loecita Sandiar; Dwi Narsih (LP2M STIT Palapa Nusantara, 2019)
The purpose of this Classroom Action Research (CAR) was carried out with the aim to find out the increase in social studies learning achievements of ASEAN material through the application of cooperative learning methods to class VI SDN Jatiasih Bekasi students in 2018/2019. This Classroom Action Research was carried out by applying the Jigsaw type cooperative learning model in order improve the quality of the learning process and is a concept of learning activities that help teachers in carrying out mathematics learning activities on fractions taught by trying to maximize the active role of students, especially the knowledge they have and how they are applied in everyday life. With this concept, learning outcomes are expected to be more meaningful for students. The learning process takes place naturally in the form of activities students work and experience, not transfer knowledge from teacher to student. The quality of learning is more important than learning outcomes. Classroom Action Research (CAR) is carried out in stages 2 cycles, and the results of the actions taken have been proven to be able to improve student learning outcomes / achievements in terms of classical student mastery learning in the first cycle of 53%, could increase to 74.5% in the second cycle and in terms of the average value of the evaluation results of 74.5 in the second cycle of 79.2, this means there is an increase of 22%. From the results of this class action research also showed an increase in the level of student learning activities from 3 categories Active Enough in the first cycle to 3.5 Active categories, Active categories in the second cycle to 3.8 categories Very Active means there was an increase of 28.5%.